The Existence of Pesantren in The Dutch East Indies Government Pressure - Fahruddin Fahruddin (IAIN Ponorogo, 2020)
Academic anxiety in this article is that pesantren, as the oldest Islamic religious education institution in the Nusantara, experienced a lot of pressure during the Dutch East Indies Government through the policies it enforced. So the first problem formulation will explain the Zending school policy imposed by the Dutch East Indies Government to compete with pesantren. The second problem formulation will explain the Teacher Ordinance policy to limit pesantren scholars’ movement in teaching Islam. From the formulation of the first problem, it is explained that the Dutch East Indies Government’s efforts by providing large financial subsidies for priests and zending school students experienced success at the beginning of the period, but failed in the next period. Whereas the second problem formulation explains the imposition of strict administrative requirements before undergoing learning activities, the prohibition of study activities if the pesantren does not meet the stipulated conditions produces more students who dare to oppose colonialism, so the Dutch East Indies Government revoked the Teacher Ordinance in 1928.Kegelisahan akademik dalam artikel ini adalah pesantren sebagai lembaga pendidikan agama Islam tertua di Nusantara mengalami banyak tekanan pada masa Pemerintah Hindia Belanda melalui kebijakan-kebijakan yang diberlakukan. Maka rumusan masalah yang pertama akan menjelaskan kebijakan Sekolah Zending yang diberlakukan oleh Pemerintah Hindia Belanda untuk menyaingi pesantren. Rumusan masalah yang kedua akan menjelaskan kebijakan Ordonansi Guru untuk membatasi gerak bagi para sarjana pesantren dalam mengajarkan agama Islam. Dari rumusan masalah yang pertama menjelaskan bahwa usaha Pemerintah Hindia Belanda dengan memberikan subsidi keuangan yang besar untuk pendeta dan siswa sekolah zending mengalami keberhasilan di awal periode, namun mengalami kegagalan di periode selanjutnya. Sedangkan rumusan masalah yang kedua menjelaskan pemberlakuan persyaratan administrasi yang ketat sebelum menjalani kegiatan belajar, pelarangan kegiatan studi jika pesantren tidak memenuhi ketentuan yang telah ditetapkan justru melahirkan lebih banyak siswa yang berani menentang kolonialisme, sehingga Pemerintah Hindia Belanda mencabut Ordonansi Guru pada tahun 1928.